Bangabasi College centenary commemoration volume - Bose, P. K.; Basu, Aparajita (Calcutta : Bangabasi College, 1991)
Contributed articles.
Part in Bengali.
Includes bibliographical references and index.
Keywords: Bangabasi College (Kolkata, India) -- History